2006
DOI: 10.1080/08860220600946087
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a Fixed-Dose Combination of Trandolapril-Verapamil in Obese Hypertensive Patients Resistant to Monotherapy

Abstract: This paper sought to determine if the fixed-dose combination of trandolapril and verapamil is effective in the treatment of hypertensive obese patients resistant to monotherapy. Thirty-six hypertensive obese patients uncontrolled by monotherapy were given the combination of trandolapril-verapamil (2/180 mg) for 12 weeks. Before and after taking the drug, they self-measured their blood pressure. Patients experienced a significant reduction of blood pressure (from 178 +/- 18/100 +/- 12 mm Hg to 135 +/- 14/76 +/-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 13 publications
(10 reference statements)
0
6
0
Order By: Relevance
“…However, it was interesting that heart rate did not change with the use of the drugs combination, because this parameter usually is reduced with verapamil. We previously reported this observation (i.e., unchanged heart rate) in type 2 diabetic hypertensive and normotensive patients; this may be due to an idiosyncratic response of Mexican people (19,20).…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…However, it was interesting that heart rate did not change with the use of the drugs combination, because this parameter usually is reduced with verapamil. We previously reported this observation (i.e., unchanged heart rate) in type 2 diabetic hypertensive and normotensive patients; this may be due to an idiosyncratic response of Mexican people (19,20).…”
Section: Discussionmentioning
confidence: 75%
“…In this study, we found a greater reduction of 24 hr albuminuria with the use of the combination in type-2 diabetic hypertensive patients, even when both treatments decreased blood pressure to the same extent. The mechanism of albuminuria reduction of FDTV, unrelated to its antihypertensive effect, may be the reduction of VCAM-1 levels, which prevents leukocyte infiltration in the kidney and reduces tissue damage in diabetic rats, decreasing albuminuria (20). However, the possibility that the reduction of these inflammatory markers may lead to reduced cardiovascular and renal risk requires further experimental confirmation.…”
Section: Discussionmentioning
confidence: 89%
“…Combination therapy of calcium antagonists plus inhibitors of the renin-angiotensin-aldosterone system (RAAS) are efficacious and safe, and represent a new addition to the available antihypertensive treatment options 6,8. This combination therapy acts on several pathways that increase BP in hypertensive patients, ie, blocking the renin-angiotensin system, relaxing vascular smooth muscle, with a reduction of peripheral resistance, and both inhibitors of the RAAS and calcium antagonists can counteract the hypertensive effect of endothelin-1 9. The 2 drug families improve endothelial function and insulin resistance 6,9.…”
Section: Introductionmentioning
confidence: 99%
“…Many choices of combinations exist; however, the efficacy and safety of those combinations remain to be evaluated. 19 We focused on two widely used antihypertensive drugs, trandolapril and verapamil. Each agent has a favourable antihypertensive effect.…”
Section: Discussionmentioning
confidence: 99%
“…We reanalysed the results after excluding this study and no significant heterogeneity was found (P ¼ 0. 19 …”
Section: Sensitivity Analysismentioning
confidence: 99%